2021
DOI: 10.1136/bmjopen-2021-053542
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and its predictors among older adults prior to and during the COVID-19 pandemic: cross-sectional and longitudinal survey findings from participants of the Atherosclerosis Risk in Communities (ARIC) Study cohort in the USA

Abstract: ObjectivesWe aimed to ascertain the prevalence of perceived loneliness among older adults following the onset of the COVID-19 pandemic and to examine factors contributing to the perception of loneliness.DesignCross-sectional and longitudinal data from the Atherosclerosis Risk in Communities (ARIC) Study cohort.SettingThe ARIC Study cohort, a prospective cohort that recruited (1987–1989) participants from four distinct communities in the USA.Participants2984 ARIC cohort members.Primary and secondary outcomesPer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(80 reference statements)
1
3
0
Order By: Relevance
“…Our finding, which indicated that young age could be associated with increased levels of loneliness, is similar to that of a large representative study of a US population 6. However, other studies have observed that old individuals experienced higher levels of loneliness during the pandemic compared with young individuals,1 7 10 25 while some studies did not find an association between age and the level of loneliness 2 3 5. Thus, the association between age and loneliness during the pandemic need further investigation.…”
Section: Discussionsupporting
confidence: 87%
“…Our finding, which indicated that young age could be associated with increased levels of loneliness, is similar to that of a large representative study of a US population 6. However, other studies have observed that old individuals experienced higher levels of loneliness during the pandemic compared with young individuals,1 7 10 25 while some studies did not find an association between age and the level of loneliness 2 3 5. Thus, the association between age and loneliness during the pandemic need further investigation.…”
Section: Discussionsupporting
confidence: 87%
“…Weissbourd et al [11], Wickens et al [17], Bu et al [13], and Li and Wang [18] evidenced that younger people became lonelier during the pandemic, while Khan and Kadoya [2] and Luchetti et al [14] reported slightly higher loneliness among older people. Tillberg et al [19] and Kucharska-Newton et al [20], in particular, provided evidence of an increasing loneliness among the older people. Furthermore, Wickens et al [17], Khan and Kadoya [2], Seifert and Hassler [21], and Bu et al [13] discovered that women were more vulnerable to loneliness, but Stickley and Ueda [22] discovered that men were more likely to be lonely.…”
Section: Introductionmentioning
confidence: 97%
“…The pandemic was a time when our participants may have been surrounded by a lot of negative stimuli, and therefore EA’s indirect effect on loneliness through neuroticism may also have come into play, as higher EA and higher neuroticism lead to loneliness and the absence of neuroticism can predict lower loneliness [ 63 ]. To combat negative stimuli, older adults may have used emotional skills associated with EA and PR to maintain high-quality social relationships during the pandemic [ 50 ]. The ability to remain connected with friends and family through technology, sharing positive experiences, social solidarity, the ability to seek support, and generally having a positive mindset as well as applying previously learned skills may all have attributed to EA links with lower loneliness and higher PR [ 51 - 53 ].…”
Section: Discussionmentioning
confidence: 99%